Manajemen Strategi Pondok Pesantren dalam Upaya Mencetak Hafidz Quran di Kabupaten Bandung - Somantri, Eli (Tadbir: Jurnal Manajemen Dakwah, 2023)
Pondok Pesantren is a place for Muslims to study the Qur'an, so that in its development, Islamic Boarding Schools have given birth to many generations of Qur'ans as a sign of progress in Islamic education. This study aims to analyze strategic management which consists of formulation, implementation and evaluation of strategies at the Al-Ilham Bojongsoang Inspiring Islamic Boarding School in Bandung in order to print the hafidz of the Quran. The method used is descriptive method with a qualitative approach. Data collection techniques through observation, interviews, and documentation studies. The results of the research show the formulation of a strategy that explores the background of the formulation of the vision through its various missions, analyzing environmental SWOT, and making general and specific strategies, implementing strategies for various tahfidzhul Quran programs, forming a student council organization, as well as performance training for management, strategy evaluation is carried out to find out success in the process of strategy formulation and implementation, to find out what needs to be improved and maintained.